Dextrophropoxyphene effects on QTc-interval prolongation: Frequency and characteristics in relation to plasma levels - Keller, Guillermo Alberto (2018)
Objective: To evaluate frequency and risk factors for dextropropoxypheneinduced QT-interval prolongation in the clinical setting. Design: Prospective, noninterventional, observational, longitudinal cohort approach. Electrocardiograms were blindly evaluated by independent professionals. Setting: General ward of a public hospital of metropolitan Buenos Aires. Patients, Participants: Ninety-two patients with indication of receiving dextropropoxyphene for analgesic purposes were included consecutively. All patients finished the study. Interventions: All patients were monitored with electrocardiographic controls (previous to drug administration and during steady state) to diagnose and quantify changes in the duration of the QTc interval. Main Outcome Measure: Frequency of drug-induced QTc interval prolongation, QTc interval correlation with plasma drug, and metabolite levels. Results: Ninety-two patients were studied (50 percent males). All patients received a (mean ± SD [range]) dextropropoxyphene dose of 125 ± 25[100-150] mg/d. Dextropropoxyphene and norpropoxyphene concentrations were 112 ± 38[45-199] and 65 ± 33[13-129] ng/mL, respectively. The intra-treatment QTc interval was >450 ms in only one patient (only with the Hodge correction). There were no cases of QTc > 500 ms, and there were no significant differences in the results considering different correction formulas (Bazzet, Fridericia, Framingham, Hodges). Dextropropoxyphene concentrations correlated with QTc (R > 0.45) interval and ΔQTc (R 0.52-0.87), whereas norpropoxyphene correlation was even greater for QTc (R > 0.40-0.64) and ΔQTc (R > 0.47-0.92). Depending on the QTc correction formula, eight patients presented ΔQTc > 30 ms and one patient with ΔQTc > 60 ms. No patient presented arrhythmia during the study. Conclusions: The authors did not observe a relationship between dextropropoxyphene and QTc interval prolongation at the therapeutic doses used in Argentina.